2007
DOI: 10.1097/qad.0b013e3282f09876
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and determinants of mortality and morbidity following early antiretroviral therapy initiation in HIV-infected adults in West Africa

Abstract: These data give new arguments to reinforce the hypothesis that, in this region, ART should be started before the CD4 cell count drops below 350 cells/mul. Further studies should assess whether patients with low BMI, low haemoglobin, high viral load or past history of tuberculosis should start ART earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
101
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(124 citation statements)
references
References 27 publications
(35 reference statements)
21
101
2
Order By: Relevance
“…4 Low body mass index (BMI < 18 kg/m 2 ) has also been associated with early mortality. [6][7][8][9][10][11][12][13] Unfortunately, only 45% of HIVinfected people know their status, which contributes to the still significant proportion (30%) with a CD4 count < 100 cells/μL at presentation despite raising the CD4 threshold for initiating treatment particularly in men. 14,15 Tuberculosis (TB) is a common cause of ART-associated death [16][17][18] among HIV-infected people in SSA, particularly in east and southern Africa.…”
Section: Introductionmentioning
confidence: 99%
“…4 Low body mass index (BMI < 18 kg/m 2 ) has also been associated with early mortality. [6][7][8][9][10][11][12][13] Unfortunately, only 45% of HIVinfected people know their status, which contributes to the still significant proportion (30%) with a CD4 count < 100 cells/μL at presentation despite raising the CD4 threshold for initiating treatment particularly in men. 14,15 Tuberculosis (TB) is a common cause of ART-associated death [16][17][18] among HIV-infected people in SSA, particularly in east and southern Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other studies in Ethiopia [27,31] showed that there is higher mortality in patients with lower baseline functional status similar to the present study. Two other studies in Africa showed that patients who experienced severe morbidity and hence poor performance at presentation to health facilities had higher risks of mortality [32,33] highlighting the need for early presentation and screening for HIV as well as TB of the general population in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…UNMASKING TB-IRIS High TB incidence rates (5.6-23 TB cases per 100 person-yrs) in the first 3 months of ART have been reported in developing country ART programmes [246,247]. TB is an important cause of the high mortality observed during early ART in these settings [248].…”
Section: Tb-associated Immune Reconstitution Inflammatory Syndromementioning
confidence: 99%